Analysis of the phenotypic abnormalities in lymphoedema-distichiasis syndrome in 74 patients with FOXC2 mutations or linkage to 16q24. Issue 7 (1st July 2002) - Brice, G; Mansour, S; Bell, R; Collin, J R O; Child, A H; Brady, A F; Sarfarazi, M; Burnand, K G; Jeffery, S; Mortimer, P; Murday, V A
Abstract : Introduction: Lymphoedema-distichiasis syndrome (LD) (OMIM 153400) is a rare, primary lymphoedema of pubertal onset, associated with distichiasis. Causative mutations have now been described in FOXC2, a forkhead transcription factor gene. Numerous clinical associations have been reported with this condition, including congenital heart disease, ptosis, varicose veins, cleft palate, and spinal extradural cysts. Subjects: We report clinical findings in 74 affected subjects from 18 families and six isolated cases. All of them were shown to have mutations in FOXC2 with the exception of one family who had two affected subjects with lymphoedema and distichiasis and linkage consistent with the 16q24 locus. Results: The presence of lymphoedema was highly penetrant. Males had an earlier onset of lymphoedema and a significantly increased risk of complications. Lymphatic imaging confirmed the earlier suggestion that LD is associated with a normal or increased number of lymphatic vessels rather than the hypoplasia or aplasia seen in other forms of primary lymphoedema. Distichiasis was 94.2% penetrant, but not always symptomatic. Associated findings included ptosis (31%), congenital heart disease (6.8%), and cleft palate (4%). Other than distichiasis, the most commonly occurring anomaly was varicose veins of early onset (49%). This has not been previously reported and suggests a possible developmental role for FOXC2 in both venous and lymphatic systems. This is the first gene that has been implicated in the aetiology of varicose veins. Conclusion: Unlike previous publications, the thorough clinical characterisation of our patients permits more accurate prediction of various phenotypic abnormalities likely to manifest in subjects with FOXC2 mutations.